POTENSI SOSIAL BUDAYA MASYARAKAT DUSUN CETHO SEBAGAI EMBRIO EKOWISATA RAKYAT DI KABUPATEN KARANGANYAR - Emy Wuryani; Wahyu Purwiyastuti (Satya Widya, 2012)
Ecotourism is not the matter of ecology and economics, but also the evaluation and opinions from society. That means it suppose to be managed by them which is starting from the planning, implementation, and benefit of it. The popularity of Cetho village society who live around the Cetho Temple seem are unprofitable by the exotic of that temple. The exotic of the temple indeed hasbeen a big attraction for the domestic and foreign tourists. As a matter of fact that is interesting to be observed. Therefore, the problem is to be observed in this research is what are the potential resources of socio-culture in Cetho village, and how the Government and Tourism Organization Motivator have made the potential resources from this society. The result of this research that 1)Beganjuran Art (the Balinese instrument in procession the Balinese dance in the Hinduism ritual)in Cetho Temple, the story and legend of Cetho Hinduism was the ancestor of Balinese Hinduism People. 2) The ritual of voluntary collective work or mutual aid every Sunday morning is a solidarity among them. 3) Cetho people say, the contribution for them which is done by the Goverment not yet maximal. According to the Tourism Service of Karanganyar Regency, the contribution has been given only for facility and in helping to propagate the potency of society. If the tourism activity will be used of course that very depends to the budget plan from central government, such as through the tourism PNPM programme.